Changes in working memory performance and cortical activity during acute aerobic exercise in young adults - Zheng, Kefeng; Deng, Zhangyan; Qian, Jiali; Chen, Yanxia; Li, Shiyuan; Huang, Tao (Frontiers in Behavioral Neuroscience, 2022)
This study aimed to examine the concurrent performance of working memory and cortical activity during acute aerobic exercise in young adults. In a crossover study design, 27 young adults (mean age = 22.7 ± 3.4 years, 15 women) participated in two experimental conditions in a randomized order: (1) sitting condition (without exercise) and (2) cycling condition (moderate-intensity exercise). Working memory was measured with a modified version of the n-back task. A functional near-infrared spectroscopy (fNIRS) was used to measure cortex activation. In the cycling condition, response time (RT) for the n-back task was significantly faster (p < 0.05). No differences in accuracy were observed between the sitting and cycling conditions. The fNIRS results showed that the oxygenated hemoglobin (oxy-Hb) concentrations in the bilateral frontopolar area (p < 0.05), dorsolateral prefrontal cortex (p < 0.05), and right premotor and supplementary cortex (p < 0.05) were decreased while cycling. The findings indicated that the concurrent performance of working memory was improved during acute aerobic exercise, whereas cortical activity was decreased in some brain regions.